Genetically detoxified tetanus toxin as a vaccine and conjugate carrier protein. Issue 35 (19th August 2022) - Chang, Min-Ju; Ollivault-Shiflett, Morgane; Schuman, Richard; Ngoc Nguyen, Son; Kaltashov, Igor A.; Bobst, Cedric; Rajagopal, Shalini P.; Przedpelski, Amanda; Barbieri, Joseph T.; Lees, Andrew
Highlights: Production of a genetically detoxified, full-length tetanus toxin protein (8MTT) in Gor/MetTM E. Coli, a strain which expresses of soluble, disulfide-bonded proteins. 8MTT was purified to > 99 % purity, yielding 0.5 g of 8MTT/liter of fermentation broth, with low. Endotoxin contamination, and antigenic purity of 3500 Lf/mg of 8MTT protein nitrogen. 8MTT is an antigenicvaccine and an effective carrier protein for peptide and polysaccharide conjugates. These studies validate 8MTT as a tetanus vaccine with modern manufacturing, regulatory, standardization, and safety requirements. Abstract: Tetanus toxoid (TTxd), developed over 100 years ago, is a clinically effective, legacy vaccine against tetanus. Due to the extreme potency of native tetanus toxin, manufacturing and regulatory efforts often focus on TTxd production, standardization, and safety, rather than product modernization. Recently, a genetically detoxified, full-length tetanus toxin protein (8MTT) was reported as a tetanus vaccine alternative to TTxd (Przedpelski et al. mBio, 2020). Here we describe the production of 8MTT in Gor/Met TM E. coli, a strain engineered to have an oxidative cytoplasm, allowing for the expression of soluble, disulfide-bonded proteins. The strain was also designed to efficiently cleave N -terminal methionine, the obligatory start amino acid for E. coli expressed proteins. 8MTT was purified as a soluble protein from the cytoplasm in a two-column protocol to > 99 % purity, yielding 0.5 g of purified 8MTT/liter of fermentation broth with low endotoxin contamination, and antigenic purity of 3500 Lf/mg protein nitrogen. Mouse immunizations showed 8MTT to be an immunogenic vaccine and effective as a carrier protein for peptide and polysaccharide conjugates. These studies validate 8MTT as commercially viable and, unlike the heterogenous tetanus toxoid, a uniform carrier protein for conjugate vaccines. The development of a recombinant, genetically detoxified toxin produced in E. coli aligns the tetanus vaccine with modern manufacturing, regulatory, standardization, and safety requirements.